Using Islamic Finance for Infrastructure projects in non-Muslim Countries - Biancone, Paolo Pietro; Shakhatreh, Mohammad Ziad (European Journal of Islamic Finance, 2015)
Using Islamic project finance is the solution to fill the gap between infrastructure demand and available finance. This study aims to investigate if it is appropriate to use Islamic finance to fund the infrastructure project, as one specific sector that is facing major challenges in long-term financing, and it intends to select the most appropriate instrument that is inconsistent with Non-Muslim countries’ law and culture. The methodology and approach that will be used is a qualitative method which is used to study the Islamic financial tools, compare them with other financial instruments, and discuss the potential implementation of Islamic project finance structure to fund the infrastructure project in Italian environment. The study concentrates on exploring the Italian laws that are resembled to Shariah principle in order to make it more acceptable for the Italian culture. The study concludes that using Islamic finance can be used to finance infrastructure projects by using existing laws and regulations. This study is also expected to benefit the Italian government and investors in making their financial decision, and it will be a new experience for Europe countries.